2011
DOI: 10.1029/2010jc006797
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variation in wave attenuation overZostera noltii

Abstract: [1] Wave attenuation is a recognized function of sea grass ecosystems which is believed to depend on plant characteristics. This paper presents field data on wave attenuance collected over a 13 month period in a Zostera noltii meadow. The meadow showed a strong seasonality with high shoot densities in summer (approximately 4,600 shoots/m 2 ) and low densities in winter (approximately 600 shoots/m 2 ). Wave heights and flow velocities were measured along a transect at regular intervals during which the site was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 52 publications
7
87
0
1
Order By: Relevance
“…4), but the trends for shoot densities ≤2000 m −2 did not differ significantly. This finding agrees with observations made in the field, where a minimum shoot density was required to observe wave attenuation in Zostera noltii (Paul & Amos 2011) and Ruppia maritima (Newell & Koch 2004). However, it may be an artefact of the dataset, as data for 2000 shoots m −2 did not show good correlation (R 2 = 0.15) and the density of 4000 shoots m −2 lacks data for a submergence ratio of 1:1.…”
Section: Submergence Ratio and Laisupporting
confidence: 91%
See 1 more Smart Citation
“…4), but the trends for shoot densities ≤2000 m −2 did not differ significantly. This finding agrees with observations made in the field, where a minimum shoot density was required to observe wave attenuation in Zostera noltii (Paul & Amos 2011) and Ruppia maritima (Newell & Koch 2004). However, it may be an artefact of the dataset, as data for 2000 shoots m −2 did not show good correlation (R 2 = 0.15) and the density of 4000 shoots m −2 lacks data for a submergence ratio of 1:1.…”
Section: Submergence Ratio and Laisupporting
confidence: 91%
“…As a result of changing water depth, wave height and period are likely to have changed. Paul & Amos (2011) showed that waves of different periods are attenuated differently by a Zostera noltii bed, and it is possible that this response to differing wave periods is responsible for the difference in wave-attenuation capacity with varying water depth. Fonseca & Cahalan (1992) varied water depth during their laboratory study on 4 different seagrass species, and al though they applied waves with the same period, incident wave height varied between runs.…”
Section: Submergence Ratio and Laimentioning
confidence: 99%
“…Most studies investigating the impact of vegetation on coastal hydrodynamics have been performed over short durations and in the summer months, when above-ground biomass is high and incident wave conditions are slight to moderate (Paul andAmos 2011, Jadhav andChen 2012). Field studies on unidirectional and channelled flows have also tended to focus on low or moderate discharges, due to difficulties associated with planning field campaigns to measure highly unpredictable events (Bakry et al 1992 and references therein).…”
Section: Examples Of Knowledge Gapsmentioning
confidence: 99%
“…This method can be cumbersome and the results cannot be translated over to other species easily (Bouma et al 2010), and needs to be performed on each species or plant morphology (USACE 2006). Even within a single species, the seasonal changes in plant foliage influence the bulk canopy drag (Schoneboom and Aberle 2009), so testing at several different stages of growth is needed to fully characterize some species (Paul and Amos 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Use of a non-dimensional drag coefficient is advantageous as it is independent of plant area, which may change seasonally, but is dependent on the morphology and hydrodynamics. For Thalassia testudinum (Bradley and Houser 2009), Zostera noltti (Paul and Amos 2011), and artificial kelp (Kobayashi et al 1993;Mendez et al 1999), exponential functions of Reynolds number were determined for the estimation of drag coefficients with reasonable accuracy.…”
Section: Introductionmentioning
confidence: 99%